InCIEC 2015 Proceedings of the International Civil and Infrastructure Engineering Conference - Yusoff, Marina; Abdul Hamid, Nor Hayati; Arshad, Mohd Fadzil; Arshad, Ahmad Kamil; Mohd Ridzuan, Ahmad Ruslan; Awang, Haryati (Springer Nature Singapore : Imprint: Springer, 2016)
The special focus of these proceedings is on the areas of infrastructure engineering and sustainability management. They provide detailed information on innovative research developments in construction materials and structures, in addition to a compilation of interdisciplinary findings combining nano-materials and engineering. The coverage of cutting-edge infrastructure and sustainability issues in engineering includes earthquakes, bioremediation, synergistic management, timber engineering, flood management and intelligent transport systems.